OTULIN is a new target of EA treatment in the alleviation of brain injury and glial cell activation via suppression of the NF-κB signalling pathway in acute ischaemic stroke rats - Hongbei Xu; You Wang; Yong Luo (BMC, 2021)
Abstract Objective Ovarian tumour domain deubiquitinase with linear linkage specificity (OTULIN) is a potent negative regulator of the nuclear factor-κB (NF-κB) signalling pathway, and it plays a strong neuroprotective role following acute ischemic stroke. Electroacupuncture (EA) is an effective adjuvant treatment for reducing brain injury and neuroinflammation via the inhibition of NF-κB p65 nuclear translocation, but the underlying mechanism is not clear. The present study investigated whether OTULIN was necessary for EA to mitigate brain injury and glial cell activation in a transient middle cerebral artery occlusion (tMCAO) model in rats. Methods An acute ischaemic stroke model was established via tMCAO surgery in Sprague-Dawley (SD) rats. EA was performed once daily at "Baihui (GV 20)", "Hegu (LI 4)", and "Taichong (LR 3)" acupoints. The effect of EA on the spatiotemporal expression of OTULIN in the ischaemic penumbra of the cerebral cortex was detected within 7 days after reperfusion. The effects of OTULIN gene silencing on EA neurological deficits, cerebral infarct volume, neuronal damage, the activation of microglia and astrocytes, the contents of tumour necrosis factor alpha (TNF-α), interleukin-1 beta (IL-1β) and interleukin-6 (IL-6), and the expression of p-IκBa, IκBa and nucleus/cytoplasm NF-κB p65 protein were assessed. Results EA treatment increased endogenous OTULIN expression, which peaked at 48 h. Enhanced OTULIN was primarily located in neurons, but a small amount of OTULIN was detected in microglia. OTULIN silencing obviously reversed EA neuroprotection, which was demonstrated by worsened neurobehavioural performance, cerebral infarct volume and neuronal injury. The inhibitory effect of EA on the NF-κB pathway was also attenuated by enhanced IκBα phosphorylation and NF-κB p65 nuclear translocation. EA partially inhibited the transformation of microglia and astrocytes from resting states to activated states and reduced the secretion of TNF-α, IL-1β and IL-6. However, these preventive effects were reversed after the silencing of OTULIN expression. Conclusions OTULIN provides a new potential therapeutic target for EA to alleviate acute ischaemic stroke-induced brain injury and the activation of glial cells, which are related to suppression of the NF-κB signalling pathway.